Let $x=r \cos \theta, y=r \sin \theta$. Which of the following expression is equal to $\left( \frac{\partial \theta}{\partial r} \right)_x$, the partial derivative of $\theta$ with respect to $r$, keeping $x$ constant.

A) $r^{-1}\tan \theta$

B) $-r^{-1} \tan \theta$

C) $r^{-1}\cot \theta$

D) $-r^{-1}\cot \theta$

E) $-r^{-1}\csc \theta$

This question seems wrong what is the relation between $\theta$ and $r$? This question for me similar to what is $\frac{\partial y}{\partial x}$


$x=r \cos \theta$

$x/r = \cos \theta$

$${\partial(x/r)\over \partial r} = {\partial \cos \theta \over \partial r}$$

$$-xr^{-2} = {\partial \cos \theta / \partial \theta \over \partial r/ \partial \theta}\tag{1}$$

$$xr^{-2} = {\sin \theta \over \partial r/ \partial \theta} $$

$$xr^{-2} = { \partial \theta \over \partial r }\sin\theta\tag{2}$$

$${x\over r \times r\sin \theta} = { \partial \theta \over \partial r }$$

$${x\over y}r^{-1} = { \partial \theta \over \partial r }$$

$$r^{-1}\cot \theta = { \partial \theta \over \partial r }$$

(1) - chain rule

(2) - inverse function rule.


When $x$ is held constant, $$ r=\frac{x}{\cos\theta}\implies \frac{\partial r}{\partial \theta}=\frac{x\sin \theta}{\cos^2\theta}\implies \frac{\partial \theta}{\partial r}=\frac{\cos^2\theta}{x\ \sin \theta}. $$ Plugging in $x=r\cos \theta$ then gives $$ \frac{\partial \theta}{\partial r}=\frac{\cos^2\theta}{r\cos\theta\ \sin \theta}=\frac{\cot\theta}{r}, $$ option (c).


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.